2019
DOI: 10.1111/gcb.14681
|View full text |Cite
|
Sign up to set email alerts
|

Modeling optimal responses and fitness consequences in a changing Arctic

Abstract: Natural selection acts across several interacting processes, including survival, mate-finding, foraging, and reproduction. Individuals must balance a series of trade-offs, whether through behavioral means or physiological adaptations. For example, an individual may need to choose between two possible foraging patches, taking into account the food available as well as the risk of predation in each

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 61 publications
(80 reference statements)
3
31
0
Order By: Relevance
“…Studies on polar bear habitat use have identified selection for intermediate to high sea ice concentrations over the shallow continental shelf, which is a biologically productive region (Durner et al 2009;Laidre et al 2018;Lone et al 2018b). Sea ice can be further categorized as stable landfast ice or active sea ice, which differ in their availability of prey (Stirling et al 1993;Pilfold et al 2016;Reimer et al 2019). Landfast ice is lower-quality foraging habitat where ringed seal pups and adults in birth lairs are hunted by polar bears (Smith and Stirling 1975;Smith 1980;Stirling et al 1993;Reimer et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on polar bear habitat use have identified selection for intermediate to high sea ice concentrations over the shallow continental shelf, which is a biologically productive region (Durner et al 2009;Laidre et al 2018;Lone et al 2018b). Sea ice can be further categorized as stable landfast ice or active sea ice, which differ in their availability of prey (Stirling et al 1993;Pilfold et al 2016;Reimer et al 2019). Landfast ice is lower-quality foraging habitat where ringed seal pups and adults in birth lairs are hunted by polar bears (Smith and Stirling 1975;Smith 1980;Stirling et al 1993;Reimer et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sea ice can be further categorized as stable landfast ice or active sea ice, which differ in their availability of prey (Stirling et al 1993;Pilfold et al 2016;Reimer et al 2019). Landfast ice is lower-quality foraging habitat where ringed seal pups and adults in birth lairs are hunted by polar bears (Smith and Stirling 1975;Smith 1980;Stirling et al 1993;Reimer et al 2019). In contrast, active sea ice is high-quality foraging habitat along leads between the fast ice and drifting offshore ice and is the habitat where juvenile/adult ringed seals and bearded seals are available to polar bears (Stirling and Archibald 1977;Stirling et al 1993;Amstrup et al 2000;Pilfold et al 2014;Reimer et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the estimated daily salmon requirement for SRKWs (~1,204 to 1,445 fish; Ford, Wright, et al, 2010) is not being met, it seems likely that fewer SABs in times of low prey abundance reflects decreased energy reserves and/or may represent a trade‐off between foraging behavior and nutritional stress as examined in other studies [e.g., green sea turtles ( Chelonia mydas ), Heithaus et al., 2007; polar bears ( Ursus maritimus ), Reimer et al. (2019); and, the fruit fly ( Drosophila melanogaster ), Billings et al., 2019). Nevertheless, the true significance of the “fewer salmon‐fewer SABs” relationship in the SRKWs remains to be seen, creating an impetus for further behavioral research in this area.…”
Section: Discussionmentioning
confidence: 97%
“…In some applications of SDP, one is interested in the temporal aspects of the optimal decisions, especially near some terminal time; these are finite time horizon problems. For example, we may expect an individual to make riskier foraging decisions near the end of a feeding season (Bull, Metcalfe, & Mangel, 1996;Reimer, Mangel, Derocher, & Lewis, 2019a). In many cases, the optimal decisions are stationary (i.e.…”
Section: Introductionmentioning
confidence: 99%